Beverage- and brand-specific binge alcohol consumption among underage youth in the US. (October 2015) - Naimi, Timothy S.; Siegel, Michael; DeJong, William; O'Doherty, Catherine; Jernigan, David
Abstract Background and objectives: Binge drinking is a common and risky pattern of alcohol consumption among youth; beverage- and brand-specific consumption during binge drinking is poorly understood. The objective of the study was to characterize beverage- and brand-specific consumption associated with binge drinking among underage youth in the US. Methods: An Internet panel was used to obtain a sample of 1032 underage youth aged 13–20, who drank alcohol in the last 30 d. For each brand consumed, youth reported drinking quantity and frequency, and whether they engaged in binge drinking with that brand (≥5 drinks for males and ≥4 for females). Each youth reporting binge drinking with a brand constituted a binge drinking report. Results: Overall, 50.9% of youth binge drank with ≥1 brand, and 36.5% of youth who consumed any particular brand reported binge drinking with it. Spirits accounted for 43.8% of binge drinking reports. Twenty-five brands accounted for 46.2% of binge drinking reports. Many of these brands were disproportionately associated with binge drinking relative to their youth market share. Conclusions: Binge drinking among youth is most commonly involves spirits, and binge drinking is concentrated within a relatively small number of brands. Understanding factors underlying beverage and brand preference among binge drinking youth could assist prevention efforts.